2019
DOI: 10.1161/circimaging.119.009178
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Computer Simulation of Transcatheter Aortic Valve Replacement in Bicuspid Aortic Valve Morphology

Abstract: Background: A patient-specific computer simulation of transcatheter aortic valve replacement (TAVR) in tricuspid aortic valve has been developed, which can predict paravalvular regurgitation and conduction disturbance. We wished to validate a patient-specific computer simulation of TAVR in bicuspid aortic valve and to determine whether patient-specific transcatheter heart valve (THV) sizing and positioning might improve clinical outcomes. Methods: A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…One potential solution for identifying patients whose anatomy may not be suitable for TAVR, is patient-specific computer simulation. This technology has been well--13-validated in the trileaflet cohort (9-11) with encouraging early validation in BAV patients (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…One potential solution for identifying patients whose anatomy may not be suitable for TAVR, is patient-specific computer simulation. This technology has been well--13-validated in the trileaflet cohort (9-11) with encouraging early validation in BAV patients (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, localization of the problematic area of the valve may have an impact on valve prosthesis selection. Additionally, the combination of radial presentation data with the more frequently described personalized simulations of the TAVR procedure (28)(29)(30)(31) may affect both device selection and design.…”
Section: Discussionmentioning
confidence: 99%
“…The company then reconstructs the cardiac anatomy, generates and runs the finite element analysis and CFD simulations, and provides a report on the results of several scenarios within two working days. Since the first presentation of this tool, numerous studies have demonstrated its clinical usage including for implantation in bicuspid aortic valves, [71][72][73] and the use of TAVI in the mitral location with native calcified valves 74,75 and inside a failed bioprosthetic valve. 76 Use of the FEops HEARTguide has also been expanded to additional TAVI devices, 77 device optimization, 78 and also for procedural recommendations based on additional possible complications, such as conduction abnormalities.…”
Section: Patient-specific Pre-procedural Planning Based On Numerical mentioning
confidence: 99%